Developing Narrative Text Material Integrated on Kurikulum Merdeka at MAN Labuhanbatu - Harahap, Nurhanna; Rusli, Muhammad; Lestari, Rizki; Hasibuan, Khoiria Rahmadani; Pasaribu, Endi Zunaedy (ITScience (Information Technology and Science), 2024)
The purpose of this research is to describe the process of developing narrative text integrated on kurikulum merdeka and to determine whether the product has an impact on English achievement for the tenth grades students at MAN Labuhanbatu. This research are Research and Development (R&D) by using ADDIE model. To gather information, two different kinds of questionnaires were employed and post-test. The first questionnaire was created to collect information for the needs analysis, the second to evaluate materials using professional judgment, and the last to evaluate the efficacy of the product. The created materials were deemed suitable based on the outcomes of the expert judgment. The developed narrative text materials were categorized as